Microarrays of ring-recessed disk electrodes in transient generator-collector mode: theory and experiment. - Menshykau, D; O'Mahony, A; del Campo, F; Munõz, F; Compton, R (2009)
The fabrication, characterization, and use of arrays of ring-recessed disk microelectrodes are reported. These devices are operated in generator-collector mode with a disk acting as the generator and the ring as the collector. We report experiments and simulations relating to time-of-flight experiments in which material electrogenerated at a disk is diffusionally transported to the ring. Analysis of the current transient measured at the latter when it is potentiostatted at a value to ensure diffusionally controlled "collection" is shown to sensitively reflect the diffusion coefficients of the species forming the redox couple being driven at the generator electrode. The method is applied to the ferrocene/ferrocenium couple in the room temperature ionic liquid [N(6, 2, 2, 2)][NTf(2)], and the results are found to agree with independent measurements.